Mysterious Function

Calculus Level 4

It is given that n = 1 f ( n ) ( x ) = f ( x ) \sum _{ n=1 }^{ \infty }{ f^{ (n) }\left( x \right) = } f\left( x \right) for all values of x x , where f ( n ) ( x ) f^{ (n) }\left( x \right) represents the n t h { n }^{ th } derivative of f ( x ) f\left( x \right) . If f ( 0 ) = 1 f(0)=1 , find the value of ln f ( 2 ) \ln { f\left( 2 \right) } .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Lim S.
Dec 16, 2014

f 1 ( x ) + f 2 ( x ) + . . . = f ( x ) f^{ 1 }\left( x \right) +f^{ 2 }\left( x \right) +...=f\left( x \right) --- (1)

Differentiating w.r.t. x x , f 2 ( x ) + f 3 ( x ) + . . . = f 1 ( x ) f^{ 2 }\left( x \right) +f^{ 3 }\left( x \right) +...=f^{ 1 }\left( x \right) --- (2)

Substituting (2) into (1), 2 f 1 ( x ) = f ( x ) 2f^{ 1 }\left( x \right) =f\left( x \right)

2 f 1 ( x ) f ( x ) = 1 \frac { 2f^{ 1 }\left( x \right) }{ f\left( x \right) } =1

Integrating w.r.t. x x , 2 ln f ( x ) = x + C 2\ln { f\left( x \right) } =x+C

f ( 0 ) = 1 C = 0 f(0)=1\Rightarrow C=0

f ( x ) = e x 2 f\left( x \right) ={ e }^{ \frac { x }{ 2 } }

ln f ( 2 ) = 1 \therefore \ln { f\left( 2 \right) =1 }

And Shao Hong, do try out some of my exciting problems!

Noel Lo - 6 years, 1 month ago
Noel Lo
Apr 28, 2015

Yo Shao Hong, long time no see huh! This is how I did it. I just randomly guessed f ( x ) = e k x f(x) = e^{kx} because l n f ( 2 ) ln f(2) gives you an integer so f ( x ) f(x) is probably an exponential function. We have:

f ( x ) + f ( x ) + f ( x ) . . . . = f ( x ) f'(x) + f''(x) + f'''(x).... = f(x)

k e k x + k 2 e k x + k 3 e k x + . . . = e k x ke^{kx} + k^2 e^{kx} +k^3 e^{kx}+ ... = e^{kx}

Dividing by e k x e^{kx} throughout, we have:

k + k 2 + k 3 . . . = 1 k+k^2 +k^3 ... = 1

k ( 1 + k + k 2 . . . . ) = 1 k(1+k+k^2.... )= 1

k ( 1 1 k ) = 1 k(\frac{1}{1-k}) =1 by sum to infinity

k = 1 k k = 1-k

2 k = 1 2k = 1

k = 1 2 k = \frac{1}{2} so f ( x ) = e x 2 f(x) = e^{\frac{x}{2}} .

So this means you will get an integer for l n ( 2 ) ln (2) , l n f ( 4 ) ln f(4) , l n f ( 6 ) ln f(6) and so on and so forth...

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...